Day vs. night: the importance of the circadian cycle over metacommunities and predator–prey densities. Issue 3 (2nd April 2016) - Parecis-Silva, Paulo V.; Nuvoloni, Felipe M.; Feres, Reinaldo J. F.
ABSTRACT: Hypothesizing that assembly of mites diverges between sampling periods, our goal was to verify the relative influence of day and night time, climatic parameters and seasonality on the metacommunities of mites associated with Genipa americana L. in Brazil, and on the foraging behaviour of the most abundant predator and phytophagous species. Seasonal variation was a key parameter in metacommunity structure and population dynamics. In contrast, day and night periods and climatic factors had a low importance for most of the response variables, apart from richness that was negatively influenced by temperature. Concerning the population dynamics, time period plays an important role in predator species, but not in phytophagous species. Our results showed that phytophagous mites remain on leaves during both periods, whereas predators seemed to have partitioned their habitat, since some species had a tendency to forage on leaves during the day, while others forage at night. Our finding can be an indicative of behavioural response to intraguild predation or competition. In terms of metacommunity structure and dynamics, sampling period seemed not to affect species composition since we recorded higher turnover rates among trees than between periods in a same tree.